Peace, justice and security in Ghana: The need for peace education - Kwadwo Addo Tuffuor (World Development Sustainability, 2023)
The causes of violence in Ghana, lie in inequality, exclusion and exploitation brought by both internal and international factors. The emergence of new socio-economic disparities and global trends towards pluralisation and politicisation has brought with it violence which has the tendency to result in the instability of the state. Justice is a fundamental pre-requisite of peaceful societies. The lack of access to legal justice and hence the recourse to violent, extra-legal means to redress grievances or pursue political and economic power threatens human security and sustainable peace in Ghana. Injustice, whether real or perceived is a cause, symptom and consequence of conflict. Legal justice and the rule of law are the essential basis of governance and human security. The paper addresses the interlinked issues of peace, justice and human security in a holistic, integral and multi-disciplinary fashion to identify and understand both the factors that underpin peace and those that might cause violence. It uses the human security methodology to demonstrate that, educating the citizenry in the values of peace through peace education can help promote sustainable peace in Ghana. The aims of peace education as related to human security and justice which encompasses the preserve of social, economic and political justice which are essential to the notion of positive peace are also examined. The paper then concludes with recommendations on how to ensure sustainable peace in the Ghanaian society.